THE ICON AS A SUBJECT OF RESIDENTIAL INTERIOR - Михайлова, Р. Д.; Петрук, Р. І. (Art and Design, 2020)
To identify the things-meaning role of the icon in modern housing interior as an object of cult and religious purpose, a work of art, a cultural artifact. General scientific methods of research have been applied, including chronographic, historical-comparative as well as those relating to art studies – figurative-stylistic, semantic, iconographic. Theoretical and art terminological constructions have been used for determining the conceptual apparatus of design. There have been analysed the peculiarities of the location of the icon in the living interior as a cult object, a work of art,a symbolic object,a household object according to its purpose as: a) a subject of religious worship, b) a collector's item, c) a cultural object that embodies religious, national-historical , myth ‒ poetic, figurative ‒ artistic meanings and reveals the possibilities of their implementation in design practice;the icon as a cult object and a work of art embodies the property of an object as a phenomenon, process, action, state, practical or theoretical human activity. It was studied out that the use of the icon in the interior takes into account that the imagery of the icon as an "internal form" of art highlights the place of the image in the overall structure of artistic reproduction of spiritual content and material external form, the point of embodiment of one in another – materialization of spiritual and spiritualization of material. It is concluded that the use of the icon in the interior involves understanding its objective meaning as two aspects of existence – material and spiritual. The scientific novelty consists in determining the place and meaning of the icon as a household item in terms of content, compositional and aesthetic filling of the residential environment. The proposed materials expand the understanding of the possibility of forming a modern residential interior; the results can be used in residential design practice.